Minimally invasive therapy for reconstruction of lost interdental papilla by using injectable hyaluronic acid filler - Unnati Pitale; Pritish Chandra Pal; Gauri Thakare; Manish Verma; Shikha Dhakad; Rohit Pandey (Wolters Kluwer Medknow Publications, 2021)
Background and Aim: Reconstruction of interdental papillae (IDP) is among the most difficult periodontal therapy. Papillary recession is multifactorial, and several surgical, nonsurgical, and minimally invasive techniques have been suggested. The purpose of this study was to evaluate the clinical application of injectable hyaluronic acid (HA) gel for the reconstruction of IDP in Nordland and Tarnow's Class I and II papillary recession cases. Materials and Methods: In the present in vivo clinical trial, 7 patients (2 males, 5 females) with 25 defects were selected. A volume of 0.2 ml HA gel was injected at the respective areas and massaged for 2-3 min. Photographs were obtained, and the assessment of the data was performed clinically (CP-GM, interproximal width [IPW]) and by Image analysis software (black triangle height [BTH], black triangle width [BTW]). Comparison of mean values was performed using the analysis of variance, followed by Post hoc Bonferroni test. Value of P ≤ 0.05 was considered statistically significant. Results: Application of HA gel for the reconstruction of IDP was successful in 6 months. CP-GM, BTH, IPW, and BTW showed a statistically significant difference from baseline to 3 and 6 months interval (P = 0.01). Post hoc Bonferroni test for CP-GM, BTH, BTW, and IPW revealed a statistically significant difference from baseline to 3 months (P ≤ 0.05) and 6 months (P ≤ 0.05) and a nonsignificant difference at 3-6 months (P ≥ 0.05). Conclusion: Injectable HA gel is a promising minimally invasive therapy for enhancing papillary esthetics.